An enchanting story: Adventure to Adelie land - Kelly, Sophia (New Delhi : Sterling publishers, 2013)
Erik, the little penguin, is very shy. But can he be brave like his dad, Mumble? Find out in this enchanting story!
Location: 3A
Keywords: Story